A Simple Accounting-based Valuation Model for the Debt Tax Shield - Andreas Scholze (BuR - Business Research, 2010)
This paper describes a simple way to integrate the debt tax shield into an accounting-based valuation model. The market value of equity is determined by forecasting residual operating income, which is calculated by charging operating income for the operating assets at a required return that accounts for the tax benefit that comes from borrowing to raise cash for the operations. The model assumes that the firm maintains a deterministic financial leverage ratio, which tends to converge quickly to typical steady-state levels over time. From a practical point of view, this characteristic is of particular help, because it allows a continuing value calculation at the end of a short forecast period.
urn:nbn:de:0009-20-25039
Keywords: 650; corporate income tax; cost of capital; debt tax shield; equity valuation; financial leverage; financial statement analysis; residual income valuation; Feltham-Ohlson framework; Bilanzanalyse; Steuervergünstigung; Fremdkapital; Kapitalkosten; Residualgewinn; Operations Research